From Smart City to Smart Village: Akselerasi Transformasi Digital dalam Optimalisasi Pelayanan Publik di Desa Kepatihan Kabupaten Gresik - Iswanto, Denny; Miskan (Contemporary Public Administration Review, 2025)
Village digitalization is urgent in achieving sustainable development, especially in realizing the concept of smart village. Smart village is designed as an effort to develop the village’s potential and resources through the application of digital technology in various aspects of governance. This study discusses the implementation of the smart village concept in Kepatihan Village, Menganti District, Gresik Regency, with a focus on the dimensions of smart government, smart economy, smart society, and smart infrastructure. The research used a qualitative approach method with interviews, observations, and documentation studies to obtain comprehensive data related to the information and communication technology used in the governance of Kepatihan Village. The results of the study show that Kepatihan Village has adopted various digital innovations, such as the use of the Premium Village Information System (SID) and collaboration with the Gresik Regency Communication and Informatics Agency in managing the village website. In addition, digital technology is also utilized to support local economic growth through a digital-based micro, small, and medium enterprises marketing platform. However, obstacles in the continuity of technological features training and optimization are still challenges in realizing a more effective and sustainable smart village. The conclusion of this study confirms that although digitalization steps have been implemented, it is necessary to increase human resource capacity through continuous training and strengthening the synergy between the government, community, and private sector to accelerate digital transformation of the village. With the right strategy, Kepatihan Village can continue to develop as an independent, innovative, and highly competitive village in the context of sustainable development.